Modeling and separate exclusion of disturbances in terrestrial observations - A.M. Kutnyi; V. Pavlik; T. Babich (Геофизический журнал, 2013)
The technique of a separate deletion of linear and anomalous nonlinear drift of earth tides observations for diurnal and semidiurnal waves are presented. It considerably (on the order) increases accuracy of determination of parameters of small tidal waves. It promotes the study of thin effects of dynamics of the Earth, its physical properties and internal structure.